A Decade after the 2009 Global Recession : Macroeconomic and Financial Sector Policies - Koh, Wee Chian; Yu, Shu (World Bank, Washington, DC, 2020)
Unprecedented monetary policy accommodation in advanced economies and a large, coordinated fiscal stimulus by G20 countries helped to support a solid rebound in global output right after the 2009 Global Recession. However, global growth subsequently slowed to a sluggish pace by pre-recession standards, and many emerging market and developing economies (EMDEs) have been struggling to unwind their fiscal stimulus and contain a buildup of debt. The experience of the global recession in 2009 highlights the need for well-timed, appropriately calibrated domestic stabilization policies, but also the benefits of international cooperation and coordination in support of strong and sustained global growth and financial system stability. Sound policy frameworks can help create room for stabilization policies, such as fiscal rules to safeguard fiscal sustainability or macroprudential policies and capital flow management measures to better manage systemic risks.